1995
DOI: 10.1021/cm00056a020
|View full text |Cite
|
Sign up to set email alerts
|

Titanium cluster polymers as reactive ion etch barriers

Abstract: Titanium oxide films are barriers to the reactive oxygen etching of photoresists in silicon device fabrication. Medium-sized clusters of Ti oxide-alkoxide have been isolated by Klemperer et al. as intermediates in the formation of sol-gels from Ti tetraalkoxides and water. We report that one of the clusters, Ti11013 (OiPr)ls, reacts with diols in hydrocarbon solvents to form network cluster polymers. These polymers form thin films of Ti-rich material that can be pyrolyzed to the anatase form of TiOa. Chemisorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Solution NMR spectroscopy is an efficient tool for probing the molecular environments of these clusters. Therefore, 17 O and 13 C solution NMR spectra were collected to assess the stability of the oxo−metallic core and the lability of the organic surface ligands, respectively. 71a, In the presence of water, only the larger titanium−oxo clusters can preserve their oxo core. Under the same mild hydrolysis conditions, Ti 16 O 16 (OEt) 32 starts to react slowly via its surface ethoxy groups, whereas Ti 7 O 4 (OEt) 20 is quickly destroyed to yield oxo polymers and other oligomers. 71a,− It has also been suggested that Ti 12 O 16 (OPr i ) 16 clusters do not react with water, provided that the reaction is conducted in the parent alcohol and in the presence of low quantities of water (4 equiv of water per cluster).…”
Section: Transition Metal−oxo-based Nbbs and The Resulting Hybrid Str...mentioning
confidence: 99%
See 1 more Smart Citation
“…Solution NMR spectroscopy is an efficient tool for probing the molecular environments of these clusters. Therefore, 17 O and 13 C solution NMR spectra were collected to assess the stability of the oxo−metallic core and the lability of the organic surface ligands, respectively. 71a, In the presence of water, only the larger titanium−oxo clusters can preserve their oxo core. Under the same mild hydrolysis conditions, Ti 16 O 16 (OEt) 32 starts to react slowly via its surface ethoxy groups, whereas Ti 7 O 4 (OEt) 20 is quickly destroyed to yield oxo polymers and other oligomers. 71a,− It has also been suggested that Ti 12 O 16 (OPr i ) 16 clusters do not react with water, provided that the reaction is conducted in the parent alcohol and in the presence of low quantities of water (4 equiv of water per cluster).…”
Section: Transition Metal−oxo-based Nbbs and The Resulting Hybrid Str...mentioning
confidence: 99%
“…Small titanium−oxo clusters, such as Ti 7 O 4 (OEt) 20 , are generally destroyed by alcohol nucleophilic attack . In contrast, the titanium−oxo cores of Ti 11 O 13 (OPr i ) 18 , Ti 12 O 16 (OPr i ) 16 , Ti 16 O 16 (OEt) 32 , and Ti 18 O 22 (OBu n ) 26 (Acac) 2 are stable toward ethanol, propanol, and diols. , Some of the alkoxide groups are exchanged by alcohol molecules R‘OH through transalcoholysis reactions, giving rise to new Ti n O m (OR) z - x (OR‘) x species such as Ti 16 O 16 (OEt) 24 (OPr n ) 8 80 or Ti 12 O 16 (O i Pr) 10 (OEt) 6 71a…”
Section: Transition Metal−oxo-based Nbbs and The Resulting Hybrid Str...mentioning
confidence: 99%
“…The favorable dielectric (25 ≤ κ ≤ 30) 30 and refractory , properties of TiO 2 have prompted a number of studies to develop methods for selective deposition of this oxide under ambient, aqueous conditions. For example, micropatterning of metal oxides using a sol−gel method has been achieved by employing SAMs in conjunction with microcontact printing techniques. However, these sol−gel processing techniques require a posttreatment heat cure, which can damage MOSFET devices already present on the substrate, to crystallize the as-prepared amorphous film. Sukenik and co-workers , have previously described selective deposition of TiO 2 (anatase), formed by hydrolysis of TiCl 4 in aqueous HCl solution at 80 °C, onto patterned organosiloxane SAMs bearing sulfonate functional groups.…”
mentioning
confidence: 99%
“…One alternative to polymeric resists is the use of a thin, protective etch layer formed from refractory metals and/or oxides. Suitable films may be derived from elements such as titanium, tungsten, zirconium, and nickel . These materials may be deposited by several deposition techniques, but electroless (EL) deposition is particularly attractive in manufacturing as it allows the low cost metallization of nonplanar, insulating substrates using low-temperature, solution-based chemistries .…”
Section: Introductionmentioning
confidence: 99%